(untitled) (Scientific journal of the Fergana State University, 2023)
The purpose of this article is to analyze the measures taken by the Soviet government in the Turkestan ASSR to eliminate illiteracy among the adult population in 1918-1922. The article shows how the initial experience of fighting illiteracy in the Turkestan ASSR was used by the Soviet government to develop a specific strategy for solving the problem. The process of eradicating illiteracy in the Turkestan Republic in the early 20s of the twentieth century was critically studied, problems and shortcomings in this process were identified. Also, new trends that emerged in the fight against illiteracy in the Turkestan ASSR in 1918-1922 were revealed. The article uses the methods of historical-chronological, comparative analysis, statistical analysis, quantitative analysis, semantic analysis and interdisciplinary approach. Information on the implementation of works and the elimination of illiteracy in the Turkestan Autonomous Soviet Socialist Republic, on the creation of schools for the elimination of illiteracy, the problems of the material and technical base and staffing of schools, and their solution are summarized.